Frailty Is Related to Subjective Cognitive Decline in Older Women without Dementia. Issue 9 (16th May 2019) - Gifford, Katherine A.; Bell, Susan P.; Liu, Dandan; Neal, Jacquelyn E.; Turchan, Maxim; Shah, Avantika S.; Jefferson, Angela L.
Abstract : OBJECTIVES: Physical frailty (or loss of physiologic reserve) is associated with cognitive impairment and dementia. Subjective cognitive decline (SCD) may represent early pathologic changes of dementia. The association between these disease markers is unclear. DESIGN: Cross‐sectional analysis. SETTING: Community‐based participants from the Vanderbilt Memory & Aging Project. PARTICIPANTS: A total of 306 older adults with normal cognition (NC; n = 174) or mild cognitive impairment (MCI; n = 132). MEASUREMENTS: Frailty was measured using standard methods, and a composite frailty score was calculated. SCD was quantified using the Everyday Cognition Scale (ECog; total score and four domain scores). Objective cognition was assessed with the Montreal Cognitive Assessment (MoCA). Proportional odds models, stratified by sex, related the frailty composite to MoCA and total ECog score adjusting for age, education, body mass index, cognitive diagnosis, depressed mood, Framingham Stroke Risk Profile, apolipoprotein E ( APOE ε4 ) carrier status, and height (for gait speed models). Secondary models related individual frailty components to SCD domains and explored associations in NC only. RESULTS: In women, frailty composite was related to MoCA (odds ratio [OR] = .56; P  = .04), a finding attenuated in sensitivity analysis (OR = .59; P  = .08). Frailty composite related to ECog total (OR = 2.27; P  = .02), planning (OR = 2.63; P  = .02), and organization scores (OR = 2.39; P  = .03). Increasing gait speed related to lower ECog total (OR = .06; P  = .003) and memory scores (OR = .03; P  < .001). Grip strength related to lower ECog planning score (OR = .91; P  = .04). In men, frailty was unrelated to objective and subjective cognition ( P values >.07). Findings were consistent in the NC group. CONCLUSION: Frailty component and composite scores are related to SCD before the presence of overt dementia. Results suggest that this association is present before overt cognitive impairment. Results suggest a possible sex difference in the clinical manifestation of frailty, with primary associations noted in women. Further studies should investigate mechanisms linking early changes among frailty, SCD, and cognition. J Am Geriatr Soc, 1–9, 2019. J Am Geriatr Soc 67:1803–1811, 2019